Crimean-congo haemorrhagic fever: a global perspective - Kalal, Nipin; ., Nimarta (International Journal of Research in Medical Sciences, 2019)
Crimean-Congo Haemorrhagic Fever (CCHF) is caused by infection with a tick-borne virus (Nairovirus) in the family Bunyaviridae, causing severe and often fatal haemorrhagic fever in humans. CCHF is pervasive, now found in Europe, Asia, Africa, the Middle East and the Indian subcontinent. CCHF spreads to humans either by tick bites or by contact with blood and tissues from infected animals or humans. CCHF outbreaks constitute a threat to public health services because of its epidemic potential, its high case fatality ratio (10-40%), and its potential for nosocomial outbreaks and its quandaries in treatment and prevention. It is characterized by sudden onset with initial sign symptoms including fever, chills, agitations, myalgia, headaches, vomiting, abdominal pain, arthralgia, ecchymosis, melena, haematuria, nose bleeding, vaginal bleeding, bradycardia, thrombocytopenia. It is diagnosed by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) assay, ELISA test, antigen detection tests. Overall supportive therapy is the mainstay of patient management in CCHF. Seriously ill patients require intensive care. Ribavirin for the treatment of CCHF cases it is most effective, if administered very soon after the onset of clinical signs (e.g., during the first 48 hours). Prevention should be taken which reduce risk of tick to human transmission and human to human transmission.